DEVELOPMENT OF A BLOCKCHAIN MODEL THROUGH A DISTRIBUTION LOGISTICS SYSTEM, PRODUCT QUALITY MONITORING, AND FARMER PARTICIPATION ON THE VALUE ADDED OF COFFEE COMMODITY IN KERINCI DISTRICT - Heppi Syofya (ITB AAS Indonesia Surakarta, 2024)
With an emphasis on how these elements collectively effect the value added of coffee in Kerinci District, Jambi, Indonesia, this study investigates how a blockchain model is established inside the distribution logistics system and how it affects farmer participation and product quality monitoring. The sample of 185 diverse participants who offered their viewpoints included coffee producers, wholesalers, processors, and consumers. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS), the study assessed the model's effectiveness. Results reveal a well-rounded demographic profile with positive attitudes on the blockchain model, distribution logistics, product quality tracking, and farmer involvement. Although significant positive correlations were found in the structural model, the measurement model demonstrated strong validity and reliability. Based on the overall goodness-of-fit indices, which indicate a satisfactory fit, the model accounts for 61% of the variance in the value added of coffee. By highlighting the critical role that technological breakthroughs, efficient logistics, quality control, and farmer involvement have in increasing total value, the results add to the body of knowledge on coffee supply chains. Keywords: Blockchain, Distribution Logistics System, Product Quality Monitoring, Farmer Participation, Value Added, Coffee Commodity, Kerinci District